2015
DOI: 10.1007/s00421-015-3276-8
|View full text |Cite
|
Sign up to set email alerts
|

Load knowledge reduces rapid force production and muscle activation during maximal-effort concentric lifts

Abstract: UC resulted in a greater initial activation of the muscles and both a higher RFD and mechanical power output in the early phase of the movement under all loading conditions (30-70 % of maximum). UC appears to offer a novel neuromuscular stimulus, and further research on the effects of continued exposure is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
4
13
1
Order By: Relevance
“…Contrary to our findings, there are also studies that found significantly increased muscular activities during PRE in unknown vs. known loading conditions . Pre‐activation and stiffness were higher in a rebound (SSC) bench press condition where the load was not known compared with where the load was known . In addition, EMG activities were increased during PRE when unknown loads were provided .…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings, there are also studies that found significantly increased muscular activities during PRE in unknown vs. known loading conditions . Pre‐activation and stiffness were higher in a rebound (SSC) bench press condition where the load was not known compared with where the load was known . In addition, EMG activities were increased during PRE when unknown loads were provided .…”
Section: Discussioncontrasting
confidence: 99%
“…The mechanism by which the use of unknown loads supposes a greater stimulus to the central nervous system may be due to a possible overestimation of the weight, causing a larger force production than that required to move the real mass [ 28 ].Our results are in accordance with the acute studies, showing that the UL group improved to a larger extent when compared to the KL group (UL: + 14.3–33.7%; KL: 8.2–21.1%) in the power developed in the early time intervals (< 150 ms). The mechanisms underlying the greater improvements of the UL group could be explained by the subject’s response to lifting unknown loads, which has been previously reported as increased EMG response in pectoralis major and anterior deltoid muscles in the early time intervals before and after the movement onset [ 27 ], which is in agreement with the increases shown by several authors in muscle activation and movement velocities when using unknown loads compared with known loads [ 17 , 29 ]. The increases in power output in the early time intervals of the movement may be explained by both an increase in motor unit firing frequency [ 30 ], and increases in motor unit recruitment due to are duced recruitment threshold of the motor units [ 31 ].…”
Section: Discussionsupporting
confidence: 83%
“…150 ms) of a movement. It has been reported that both a greater power output and muscle activation can be produced at early time intervals as an acute response of using unknown loads, when compared to known loads [ 13 , 27 ]. The mechanism by which the use of unknown loads supposes a greater stimulus to the central nervous system may be due to a possible overestimation of the weight, causing a larger force production than that required to move the real mass [ 28 ].Our results are in accordance with the acute studies, showing that the UL group improved to a larger extent when compared to the KL group (UL: + 14.3–33.7%; KL: 8.2–21.1%) in the power developed in the early time intervals (< 150 ms).…”
Section: Discussionmentioning
confidence: 99%
“…Instructions for training such as very heavy (strength-oriented), intermediate (Pmax), or very light (speed-oriented) may be a sufficient prescription, rather than aiming for precise intensity values. A recent study by Hernandez-Davo et al (2015) 72) demonstrated that lifting of unknown loads resulted in more rapid force production and greater EMG activity than those of lifting the same loads with load knowledge, despite an instruction to elicit maximum effort. It was suggested that an over-estimation of the load resulting from no-load knowledge increased the pre-programmed muscle activation (or activation preparation).…”
Section: Summary and Implicationsmentioning
confidence: 99%